METHODOLOGICAL ASPECTS STUDY OF RELIGION AND ECONOMIC RELATIONS - Дадівєріна, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to methodology and method to study the relationship of religion and the economy.